Development Of Performance Management System (Hr) In New Mart Minimarket - Tia Jesi; Antony Sentoso (Universitas Internasional Batam, 2023)
New Mart Minimarket is a business owned by Mr. Yoki Liberty which was founded on October 12 2018 and is located in the Nusa Jaya Complex Block A No. 26,27,28 Sungai Panas, Batam city. This business is engaged in retail, which sells various kinds of daily needs. The purpose of this practical work is to assist MSMEs in implementing work procedures according to company operational standards. The data collection technique used was conducting interviews and observations. The result is the application of appropriate standard operating procedures, company profiles, organizational structures, job descriptions by preparing reports and explaining to employees regarding all material so that it can assist owners in improving and maintaining the good name of the company, increasing accountability such that employees work according to their respective duties and responsibilities.